1982
DOI: 10.1111/j.1471-4159.1982.tb08647.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Uptake and Catecholamine Secretion by Cultured Bovine Adrenal Medulla Cells

Abstract: The uptake of 45Ca2+ and secretion of catecholamines by primary cultures of adrenal medulla cells were studied. Nicotine, veratridine, potassium, and Ionomycin stimulate both the accumulation of 45Ca2+ and the secretion of catecholamines. Nicotinic antagonists block 45Ca2+ uptake induced by nicotine, tetrodotoxin blocks 45Ca2+ uptake induced by veratridine, and D600 or secretion induced by Ionomycin. The EC50 for nicotine is 3 microM for catecholamine secretion and 10 microM for 45Ca2+ uptake, while the EC50s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(79 citation statements)
references
References 22 publications
4
75
0
Order By: Relevance
“…Acetylcholine (ACh) facilitated norepinephrine release from peripheral human lymphocytes, as did inflow of calcium into human lymphocytes. Yet, in clear contrast to mechanisms employed by chromaffin cells, blockade of nicotinergic receptors on lymphocytes blocked ACh-induced release of norepinephrine release only by about 50% and blocking of Ca 2+ -channels attenuated the AChinduced norepinephrine release by no more than 30% (30,31). Therefore, it is clear that we lack a detailed understand-ing of the molecular mechanisms involved in catecholamine release by lymphocytes.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Acetylcholine (ACh) facilitated norepinephrine release from peripheral human lymphocytes, as did inflow of calcium into human lymphocytes. Yet, in clear contrast to mechanisms employed by chromaffin cells, blockade of nicotinergic receptors on lymphocytes blocked ACh-induced release of norepinephrine release only by about 50% and blocking of Ca 2+ -channels attenuated the AChinduced norepinephrine release by no more than 30% (30,31). Therefore, it is clear that we lack a detailed understand-ing of the molecular mechanisms involved in catecholamine release by lymphocytes.…”
mentioning
confidence: 90%
“…Incubation of human PBMCs with reserpine markedly reduced intracellular accumulation of catecholamines, while catecholamine levels in culture supernatant fluids significantly increased (21), suggesting that human PBMCs employ a mechanism similar to neurons, resulting in catecholamine release followed by reuptake. Moreover, studies have revealed that, in accordance with chromaffin cells from the adrenal medulla, secretion of norepinephrine by human lymphocytes depends on acetylcholine and calcium (30,31). Acetylcholine (ACh) facilitated norepinephrine release from peripheral human lymphocytes, as did inflow of calcium into human lymphocytes.…”
mentioning
confidence: 99%
“…BIRMAN AND F.-M. MEUNIER & Rink, 1975) and in cultured chromaffin cells (Holz, Senter & Frye, 1982; Kilpatrick, Slepetis, Corcoran & Kirshner, 1982), as well as on the release of pituitary hormones (Nordmann, 1976;Dyball & Shaw, 1981; Tomiko, Taraskevich & Douglas, 1981) and the release of ACh from rat brain synaptosomes (Suszkiw & O'Leary, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, in cultured bovine adrenal medullary cells, nicotinic (but not muscarinic) receptors mediate the Ca 2ļ¼‹ -dependent secretion of CA Fisher et al, 1981). It has also been known that the activation of nicotinic receptors stimulates CA secretion by increasing Ca 2ļ¼‹ entry through receptor-linked and/or voltage-dependent Ca 2ļ¼‹ channels in both perfused rat adrenal glands (Wakade and Wakade, 1983;Lim and Hwang, 1991) and isolated bovine adrenal chromaffin cells (Kilpatrick et al, 1981(Kilpatrick et al, & 1982Knight and Kesteven, 1983 channels without increasing Na ļ¼‹ influx. In the present study, the finding that high K ļ¼‹ -induced CA secretory response was depressed by pretreatment with provinol indicates that this inhibitory effect of provinol is exerted through the direct inhibition of calcium influx into the rat adrenal chromaffin cells.…”
Section: Discussionmentioning
confidence: 77%